2015
DOI: 10.1071/bt14267
|View full text |Cite
|
Sign up to set email alerts
|

A geobotanical investigation of the Koedoesfontein Complex, Vredefort Dome, South Africa

Abstract: The Vredefort Dome (impact structure) in South-Africa hosts several unique peralkaline to ultramafic intrusive bodies that were emplaced into its core and collar. Because of the broad difference in mineral composition, between the intrusions as well as the abundant siliciclastic country rocks, abrupt transitions in soil chemical characteristics are produced that can ultimately affect the floristic and physiognomic characteristics of the associated vegetation in the dome. Despite various efforts to study the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A study conducted by Li et al (2015) in subtropical China, revealed separation of indicator plant species across a pH gradient in combination with other environmental variables. Therefore, soil chemical characteristics can be considered as one of the most significant factors driving floristic composition across mountain ecosystems (Boneschans et al 2015) and explain the preferences of indicator plant species associated with each mountain (Soares et al 2015).…”
Section: Species Compositionmentioning
confidence: 99%
“…A study conducted by Li et al (2015) in subtropical China, revealed separation of indicator plant species across a pH gradient in combination with other environmental variables. Therefore, soil chemical characteristics can be considered as one of the most significant factors driving floristic composition across mountain ecosystems (Boneschans et al 2015) and explain the preferences of indicator plant species associated with each mountain (Soares et al 2015).…”
Section: Species Compositionmentioning
confidence: 99%